Imputability in the patrimonial responsibility of the State in the so-called extrajudicial executions and the subsequent for public agents - Yepes Gómez, Fernando (DIXI, 2021)
Subject and scope: the last decades of Colombian history have been marked by the profound damage caused by acts of violence from subversive groups. The State's reaction has not been long in coming, and to improve the results in fighting the members of the illegal groups, it has proposed a great variety of policies to the members of the Public Force to stimulate or encourage their performance.Characteristics: first, at the end of the seventies and, later, in the first decade of the xxi century, practices that consisted of leading victims, with the support of civilian informants to simulate combats or attribute the commission of crimes to them, became widespread (indeed reported internally and externally) to obtain economic and institutional privileges for their death. This resulted in the constitution of criminal practices with the disguise of being legal (extrajudicial executions) to show efficacy and efficiency.Findings: the analysis of the State's responsibility for extrajudicial executions in Colombia has been the subject of analysis by both the highest Administrative Contentious Court and the Inter-American Court of Human Rights and has rested on the idea that legal accountability does not entail discussion.Conclusion: the violation of Colombian’s fundamental rights could not infer another judgment of disapproval to the State than that of declaring its duty to compensate the victims, given the disturbing notes of distress that also tarnish the credibility of the Public Force, since if their mission and function is to guarantee or safeguard the rights of the State, the fact of becoming the architect and promoter of these transgressions leaves a cloak of mistrust in their work, and there is a translocation of positions from insurer to infringer.
Keywords: patrimonial responsibility; extrajudicial execution; false positive; legal imputability; causality; agent personal imputability; act of service